IN VITRO ANTIVIRAL ACTIVITY OF PROANTHOCYANIDIN A2 AGAINST CANINE DISTEMPER VIRUS - Galligioni, V.; Dal Pozzo, F.; Fontana, G.; Bombardelli, E.; Baldelli, E.; Scagliarini, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Canine distemper virus (CDV) is an enveloped RNA virus, causing a highly contagious disease of domestic and wild canids as well as of other terrestrial and aquatic carnivores. Although the vaccine, outbreaks are still reported worldwide and up to date no effective treatments exist. Proanthocyanidins are flavonoids having well known antioxidant, anti-inflammatory and antimicrobial properties (1,2). In this study the in vitro antiviral activity of Proanthocyanidin A2 against CDV and its effects on viral replication were evaluated. The cytotoxicity (CC50) of Proanthocyanidin A2 was tested on growing VERO cells by the MTT assay (3). Extra- and intracellular antiviral activities (IC50) were evaluated by cytopathic effect (CPE) inhibition assay in confluent cells monolayers. In order to investigate the mechanism of action of the compound against CDV, the Time of Addition assay was carried out adding at several times post-infection 150, 100 or 75 Î¼g/ml of Proanthocyanidin A2, followed by virus titration. Proanthocyanidin A2 was not toxic on VERO cells (CC50>200Î¼g/ml), showing only intracellular antiviral activity (IC50=89.81Â±4 Î¼g/ml) with a selectivity index (the ratio of CC50 and IC50, SI) >2. Analysis by One way ANOVA test demonstrated that Proanthocyanidin A2 decreased the viral growth significantly (P<0.05) up to 16 hours post infection. Proanthocyanidin A2 was active against CDV with a SI greater than Ribavirin, the only compound with demonstrated anti-CDV activity, and it decreased the viral growth in a time- and concentration- dependent way.References:1- Shahat AA, Cos P. et al.,(2002) Planta Med. Jun;68(6):539-41; 2- Maldonado PD, Rivero-Cruz I, et al., (2005) J Agric Food Chem. Mar 23;53(6):1996-2001; 3- Hussain RF, Nouri AM, Oliver RT. 1993 J Immunol Methods. 1993 Mar 15;160(1):89-96;